2006
DOI: 10.1136/vr.158.10.325
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem diagnosis of preclinical and clinical scrapie in sheep by the detection of disease‐associated PrP in their rectal mucosa

Abstract: Samples of tissue from the central nervous system (cns), the lymphoreticular system (lrs) and the rectal mucosa of a large number of scrapie-exposed sheep, with and without signs of clinical disease, were examined immunohistochemically for evidence of disease-associated prion protein (PrP(d)). The rectal mucosa has received almost no attention so far in scrapie diagnosis, despite its abundant rectoanal mucosa-associated lymphoid tissue, and its accessibility. The scrapie-confirmed cases included 244 with clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 30 publications
(4 reference statements)
6
65
0
2
Order By: Relevance
“…Previous work had suggested that examination of LRS tissues in addition to brain provides better estimates of scrapie infection in sheep [13,25,28]. Our results are a noticeable example that this is also the case in goats and that, in agreement with those earlier sheep studies, the medial retropharyngeal lymph node would be the sample of choice, together with the obex, for post-mortem surveillance.…”
Section: Implications For Surveillance Of Goat Tsesupporting
confidence: 88%
See 1 more Smart Citation
“…Previous work had suggested that examination of LRS tissues in addition to brain provides better estimates of scrapie infection in sheep [13,25,28]. Our results are a noticeable example that this is also the case in goats and that, in agreement with those earlier sheep studies, the medial retropharyngeal lymph node would be the sample of choice, together with the obex, for post-mortem surveillance.…”
Section: Implications For Surveillance Of Goat Tsesupporting
confidence: 88%
“…Post-mortem detection of PrP d in the RAMALT was achieved in a low percentage [13]), and similar ones in chronic wasting disease of cervids [21,33]. Whether this is a feature of goat scrapie in general or a peculiarity of this outbreak is unknown but, in any case, the frequency of detection of PrP d in the RAMALT rises to 84.0% when goats with widespread LRS involvement -but still at preclinical stagesare considered.…”
Section: Implications For Surveillance Of Goat Tsementioning
confidence: 77%
“…Several authors have reported the use of WB to identify the PrP Sc in samples of ovine brain (O'ROURKE et al, 1998;GONZÁLEZ et al, 2006;BILHEUDE et al, 2007). However, for antemortem diagnostics using samples of lymphoid tissues, this method presents a few limitations, owing to the fact that the harvested sample shows a low amount of lymphoid follicles, thus reducing the chance of obtaining detectable amounts of PrP Sc , and increasing the probability of false negative results (LEAL et al, 2012).…”
Section: Western Blottingmentioning
confidence: 99%
“…However, these procedures are not easily performed in the field and do not allow for repeated resampling. The description of constitutive lymphoid tissue in the sheep rectum (ALEKSANDERSEN; NICANDER; LANDSVERK, 1991) prompted the use of rectal mucosa samples for the post-mortem diagnosis of scrapie (GONZÁLEZ et al, 2006), since accumulation of PrP Sc occurs in such tissue. Moreover, samples from the rectal mucosa can also be obtained using a simple and rapid biopsy technique that does not require specific instruments, sedation, or general anesthesia and that can be performed several times without any detrimental effects on the animal.…”
Section: Introductionmentioning
confidence: 99%
“…PrP Sc has been found in tissues that could be involved in the natural dissemination of the infectious agent i.e., routes that could lead to exit of the infectious agent from the animal, and result in either environmental contamination or direct transmission. These tissues include the lympho-reticular system of the gut [40,103,115], chronically inflamed mammary tissue associated with lymphocyctic mastitis [73], kidney tissue [90], salivary glands [104], nictitating membrane [77], and placentae [2,81,101].…”
Section: Alternative Disease Modelsmentioning
confidence: 99%